2006
DOI: 10.1001/jama.296.24.2947
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Proton Pump Inhibitor Therapy and Risk of Hip Fracture

Abstract: Context Proton pump inhibitors (PPIs) may interfere with calcium absorption through induction of hypochlorhydria but they also may reduce bone resorption through inhibition of osteoclastic vacuolar proton pumps.Objective To determine the association between PPI therapy and risk of hip fracture. Design, Setting, and PatientsA nested case-control study was conducted using the General Practice Research Database (1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
742
14
37

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,067 publications
(816 citation statements)
references
References 39 publications
23
742
14
37
Order By: Relevance
“…• une étude cas-témoin britannique nichée dans la cohorte General Practice Research Database (GPRD) [4], qui a conclu qu'une durée de traitement par IPP supérieure à une année était associée à un risque augmenté de fracture du col du fémur. [6].…”
Section: Risque Fracturaireunclassified
See 1 more Smart Citation
“…• une étude cas-témoin britannique nichée dans la cohorte General Practice Research Database (GPRD) [4], qui a conclu qu'une durée de traitement par IPP supérieure à une année était associée à un risque augmenté de fracture du col du fémur. [6].…”
Section: Risque Fracturaireunclassified
“…Plusieurs auteurs en ont déduit que ces fractures relevaient d'un mécanisme ostéoporotique [4,5]. Pourtant, une étude réalisée chez des volontaires sains et utilisant une mesure directe de l'absorption intestinale du calcium a montré que l'oméprazole ne modifiait pas cette absorption [10].…”
Section: Risque Fracturaireunclassified
“…(1,2) PPIs specifically target the H þ ,K þ -ATPase pump of the gastric parietal cell, thereby inhibiting the final step in gastric acid production. An emerging concern about chronic PPI therapy is that it may inhibit intestinal calcium absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about the effects of PPIs on calcium homeostasis have been heightened by two retrospective case-controlled studies that reported an increased risk of fracture in patients with long term PPI use. (1,3) A recent prospective study in 1211 postmenopausal women found that omeprazole use was associated with an increased risk of vertebral fractures. (4) Another study, however, failed to find such an association.…”
Section: Introductionmentioning
confidence: 99%
“…Many retrospective observational studies found several adverse outcomes linked to PPI therapy, including hip fracture,6 pneumonia,7 acute interstitial nephritis8 and hypomagnesemia 9. Thus, the safety of the long‐term use of PPI has recently been questioned.…”
mentioning
confidence: 99%